2015
DOI: 10.1016/j.amjmed.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Early Repolarization Pattern in Elite Athletes

Abstract: A third of elite athletes presented ERP, and this persisted in 53.4% of cases after retirement. After a long follow-up period, no difference in outcome of SCD was seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 31 publications
4
30
0
5
Order By: Relevance
“…In our study population, the prevalence of ER pattern was 29.9%, which closely corresponds to the results reported by other authors and confirms common occurrence of such ECG alterations in high endurance athletes [2,13,[25][26][27]. Despite nearly identical overall prevalence of the ER pattern, large differences in the rates of these alterations in specific leads were noted between various studies.…”
Section: Nssupporting
confidence: 77%
“…In our study population, the prevalence of ER pattern was 29.9%, which closely corresponds to the results reported by other authors and confirms common occurrence of such ECG alterations in high endurance athletes [2,13,[25][26][27]. Despite nearly identical overall prevalence of the ER pattern, large differences in the rates of these alterations in specific leads were noted between various studies.…”
Section: Nssupporting
confidence: 77%
“…Inferior (Haruta et al, 2011;Klatsky et al, 2003;Kui et al, 2008;Noseworthy et al, 2011;Serra-Grima et al, 2015;Sinner et al, 2010;Sun et al, 2017;Uberoi et al, 2011).…”
Section: Er Localizationunclassified
“…This contrasts with findings in healthy elite athletes, where the ER pattern disappears in >50% after detraining. 30 Furthermore, it is intriguing that there were no further arrhythmic events after sports discontinuation in the sudden cardiac arrest survivors. This is not in keeping with the findings from the original study by Haïssaguerre et al, 3 where recurrent arrhythmic events were common in patients with ER during follow-up.…”
Section: Er In Athletesmentioning
confidence: 99%
“…On the contrary, several studies have demonstrated a lack of an association between J waves and malignant arrhythmias in athletes during medium to long-term follow-up. [28][29][30]37 However, given the rarity of SCD in athletes (annual incidence of 1/75 000 to 1/200 000 per year), 38,39 it should be pointed out that these longitudinal studies, although some are of considerable size and length, remain underpowered. Nevertheless, after taking all of the above into account, several international expert consensus documents categorize ER, of all subtypes, as a benign ECG finding in athletes.…”
Section: Er In Athletesmentioning
confidence: 99%
See 1 more Smart Citation